Vertical stratification of peatland microbial communities follows a gradient of functional types across hummock–hollow microtopographies. Issue 3 (3rd July 2019) - Asemaninejad, Asma; Thorn, R. Greg; Branfireun, Brian A.; Lindo, Zoë
ABSTRACT: Microbes play crucial roles in global carbon cycles, particularly in peatland ecosystems that store vast quantities of carbon. Boreal peatlands are under stress from commercial extraction of peat, drainage for conversion to forestry and agricultural lands, and climate change. In this study, we identify key microbial groups and their ecological functions across peatland depth profiles and provide insight into how environmental changes related to water table may alter microbial communities. We examined the diversity and composition of prokaryotic communities across a microtopographic hummock–hollow gradient using Illumina sequencing. Communities formed a gradient of species and functional groups with depth, with overlap in functional groups at lower layers of hummocks and upper layers of hollows. Yet, overall, we found significantly different prokaryotic communities in hollows than hummocks. Surfaces of hummocks were typified by aerobic chemoorganotrophs, methanotrophs and chemoheterotrophs, mid-depths were typified by aerobic chemoorganotrophs, nitrogen-fixing bacteria and anaerobic nitrate reducers, while lower depths in hollows were typified by anaerobic and facultative anaerobic chemoorganotrophs, nitrate reducers and methanogenic archaea. Microbial composition as a function of hydrology and moisture regimes suggests that environmental changes that alter hydrological regimes (e.g., climate change, peatland draining) may alter carbon and nutrient cycling regimes.